Sob à luz dos holofotes: percursos da masculinidade hegemônica e subalternidade feminina na História - Martins, Tattiussa Costa (2022)
Entrenched in our culture with the backing of coloniality and patriarchy are hegemonic masculinity and female subalternity. Which symbolizes the pillars of our national identity and the maintenance of social order. These values introjected by the colonizers who strove to naturalize cultural constructions as something inherent to our biological nature, making it difficult to reflect that these conceptions are part of a framework of political strategies to favor the domination of a people. In this logic, conservatism is positive as a moral value that saves the homeland, confidently for the permanence of political stability and sociocultural morality.